2009
DOI: 10.1056/nejmoa0904544
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline Dose Intensification in Acute Myeloid Leukemia

Abstract: BACKGROUND In young adults with acute myeloid leukemia (AML), intensification of the anthracycline dose during induction therapy has improved the rate of complete remission but not of overall survival. We evaluated the use of cytarabine plus either standard-dose or high-dose daunorubicin as induction therapy, followed by intensive consolidation therapy, in inducing complete remission to improve overall survival. METHODS In this phase 3 randomized trial, we assigned 657 patients between the ages of 17 and 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
604
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 806 publications
(637 citation statements)
references
References 25 publications
30
604
0
3
Order By: Relevance
“…In the study involving younger patients, high-dose daunorubicin was associated with a significantly higher CR rate (71% versus 57%; p < 0.001) and longer survival (median 24 versus 16 months; p 5 0.003). But the benefit was observed only in patients younger than 50 years and those with normal karyotypes [72]. In the study of older patients, high-dose daunorubicin was associated with a higher CR rate (64% versus 54%; p 5 0.002) but not with improved survival, although a survival benefit was observed in the subset of patients 60-65 years old [94].…”
Section: Younger Patients With Amlmentioning
confidence: 88%
See 2 more Smart Citations
“…In the study involving younger patients, high-dose daunorubicin was associated with a significantly higher CR rate (71% versus 57%; p < 0.001) and longer survival (median 24 versus 16 months; p 5 0.003). But the benefit was observed only in patients younger than 50 years and those with normal karyotypes [72]. In the study of older patients, high-dose daunorubicin was associated with a higher CR rate (64% versus 54%; p 5 0.002) but not with improved survival, although a survival benefit was observed in the subset of patients 60-65 years old [94].…”
Section: Younger Patients With Amlmentioning
confidence: 88%
“…High-dose cytarabine consolidations were followed by 4 additional courses of 2 1 5 chemotherapy [71]. The latter addition has been omitted from the subsequent comparative trials, an important consideration since later studies using this regimen as the standard of care reported five-year survival rates of 20-30% rather than 40% [72]. Following the findings of this pivotal trial, high-dose cytarabine for 4 consolidations became the consolidation standard of care in AML.…”
Section: Younger Patients With Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…31 These findings were subsequently confirmed in numerous other trials. [33][34][35][36][37] In general, patients with FLT3-ITD AML achieve complete remission rates comparable to those of patients with wild-type disease, but have significantly higher rates of relapse and shorter durations of disease-free and overall survival (OS). 31,[33][34][35] In the Medical Research Council studies, patients with FLT3-ITD AML had a 74% relapse rate vs 48% for patients with FLT3-wild-type AML.…”
Section: Flt3 As a Prognostic Markermentioning
confidence: 99%
“…Recently, the use of high dose 90 mg/ m 2 daunorubicin (DNR) was reported in several phase III clinical trials to improve both complete remission (CR) rate and overall survival (OS) as compared with low dose DNR (45 mg/m 2 ) and is now considered as a standard of care [1,2]. However, the dose of 45 mg/m 2 is not used worldwide and several groups use intermediate dose of 60 mg/m 2 and reported OS of approximately 40%-45% at 5 years in younger AML patients [3,4].…”
mentioning
confidence: 99%